Sustainable resilient design challenges for ecotourism education in Setiu Wetland - Aminuddin, Balqis; Siow, May Ling; Ismail, Sumarni; Herman, Siti Sarah (Human Resource Management Academic Research Society, 2023)
In Terengganu, Malaysia, the Setiu Wetland is a protected area that is a great place to learn about the environment. There is a lot of potential for ecotourism here. One of the most effective ways to reduce harmful impacts on the environment is to offer ecotourism education at tourist spots. To protect the natural ecosystem and the cultural history of the nearby communities, wetland environmental education centres in this ecologically sensitive area must be carefully planned. This is because there are several things that need to be considered. But the lack of new and modern tourist facilities has made it hard for coastal wetland destinations to grow as tourist destinations. Both the lack of physical growth of wetland facilities and the lack of clear national policies and standards to regulate these facilities have been blamed for the drop in the number of tourists who visit wetlands. A serious problem is getting worse. Setiu Wetland needs to find out if there are any problems with the technological and architectural parts of the sites for ecotourism educational experiences. This study wants to find out if there are any gaps in the physical facility designs for ecotourism educational experiences in the Setiu Wetland so that they can be filled. This study used three methods: in-depth interviews, online and in-person observations, and planning papers. Observations by participants are also a way that data are collected. By talking to partners and authorities in-depth, the information was better. Setiu Wetland's environmental education buildings need to be designed with environmental sensitivity, accessibility, cultural sensitivity, and long-term sustainability in mind. By working closely with regional stakeholders and local communities, it is possible to build facilities that are good for the environment, protect cultural history, and give visitors an interesting and educational experience.